Maternal excessive gestational weight gain as a risk factor for autism spectrum disorder in offspring: a systematic review - Sorayya Kheirouri; Mohammad Alizadeh (BMC, 2020)
Abstract Background Abnormal gestational weight gain (GWG) is a prenatal complication that may contribute to long-term behavioral and neurodevelopmental differences in offspring. This systematic review summarizes research on the association between maternal GWG and risk of autism spectrum disorder (ASD) in offspring. Methods Google and electronic databases, including PubMed, SCOPUS, Embase, Cochrane Library and Google Scholar, were searched for original human studies published in English through June 2020. Articles that examined the association between GWG and risk of ASD in offspring were included. Duplicate and irrelevant studies were removed; and data were obtained through critical analysis. Results Of 96 articles searched, eight studies were included in the final review. All studies (n = 7) investigating the association of maternal excessive GWG with risk of ASD in offspring indicated that high GWG was independently associated with an increased risk of ASD. Of five studies investigating the association of inadequate GWG with the risk of ASD, four indicated that low GWG was not associated with an increased risk of ASD. Of seven studies examining the association of maternal pre-pregnancy BMI or weight with the risk of ASD, five reported that maternal pre-pregnancy BMI or weight did not appear to be independently associated with risk of ASD. The GWG-ASD association is independent of maternal BMI and child's intellectual disability, but offspring's genetic susceptibility connection to the GWG-ASD association remains a topic of debate. Conclusions The findings suggest that maternal excessive GWG may be associated with increased risk of ASD in offspring. However, insufficient GWG does not appear to have such association.